Strategi Dakwah Muhammadiyah Melalui FKMMS (Forum Komunikasi Masjid Muhammadiyah Sidoarjo) - Istkomah Istkomah; Dzulfikar Akbar Romadlon; Budi Hariyanto (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2020)
The focus of Muhammadiyah, as stated in its AD/ART, is the da'wa of Islam